Analysis of Immunosuppressant Drugs in Whole Blood by Liquid Chromatography–Tandem Mass Spectrometry (LC‐MS/MS). Issue 1 (21st May 2020) - Pablo, Abed H.; Breaud, Autumn R.; Clarke, William
Abstract: Immunosuppressant medications help suppress the immune system response through inhibition of various checkpoints in the regulatory biochemical pathway. This is useful in prevention of organ rejection in transplantation or in the treatment of autoimmune diseases such as lupus or rheumatoid arthritis. Quantification of immunosuppressive drugs in blood is needed clinically for optimization of treatment and to avoid toxicity or unwanted side effects. Here, we describe a quantitative method to determine the concentration of cyclosprine A, tacrolimus, sirolimus, and everolimus in whole blood. This method has been used for many years clinically to support patient care. © 2020 by John Wiley & Sons, Inc.